ANALISIS NILAI TAMBAH SAGU KASBI MENJADI SAGU KASBI ANEKA RASA (STUDI KASUS PADA KELOMPOK TANI TAGAFURA DI KELURAHAN JAYA KECAMATAN TIDORE UTARA KOTA TIDORE KEPULAUAN) - Siti Arofah,; Mila Fatmawati,; Mardiyani Sidayat, (Journal of Innovation Research and Knowledge, 2022)
Sago cassava is a typical food of northern Maluku and sago cassava with various flavors is an innovation from sago cassava to expand market share because it has many choices of flavor. This is done in order to increase added value and income. This study aims to determine how much income and added value of sago cassava and sago cassava various flavors. This research was conducted on the tagafure farmer group. With the determination of the sampel using the kenuh sampel, namely the tagafura farmer group in the jaya sub-district, Tidore city, the karens archipelago is a place for processing cassava sago and various flavors of cassava sago. The results showend that the various flavors of cassava sago were more profitable with an analysis of the acceptance of cassava sago of Rp. 40,896,000 and various flavors of sago cassava for Rp. 46,332,000. Cassava sago profit of Rp. 14,494,247.2 and sago cassava various flavors of Rp. 21,845,447.2 R/C ratio of sago cassava is Rp. 1,45 and various flavors of sago cassava for Rp. 1.89. BEP unit sago cassava as much as 330.7 kg and sago cassava various flavors 73.28 kg.BEP rupiah sago cassava Rp. 6,614 and various flavors of sago cassava for Rp. 5,239. The added value of sago cassava is Rp. 7,020/kg and various flavors of sago cassava for Rp. 13.810/kg.